1991
DOI: 10.1111/j.1442-200x.1991.tb01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Urokinase in Kawasaki Disease: Treatment and Prevention of Myocardial Infarction

Abstract: The main cause of death in Kawasaki disease is myocardial infarction due to thrombotic occlusion of a coronary aneurysm. Intracoronary thrombolytic treatment was performed in 15 patients with Kawasaki disease with giant coronary aneurysms. Three patients had acute myocardial infarction, four demonstrated silent myocardial infarction, three suffered chest pain and five did not show ischemia features but had massive thrombus in the coronary aneurysms. Urokinase was infused into the coronary aneurysms as a bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…In case reports, streptokinase, 184,185 urokinase, [186][187][188] and tissue plasminogen activator (tPA) 189,190 each has been administered to infants and children with coronary thrombosis with varying success rates (evidence level C). Because no randomized, controlled trials have been performed in children, the treatment of infants and children with coronary thrombosis is derived from studies in adults with acute coronary syndromes.…”
Section: Treatment Of Coronary Thrombosismentioning
confidence: 99%
“…In case reports, streptokinase, 184,185 urokinase, [186][187][188] and tissue plasminogen activator (tPA) 189,190 each has been administered to infants and children with coronary thrombosis with varying success rates (evidence level C). Because no randomized, controlled trials have been performed in children, the treatment of infants and children with coronary thrombosis is derived from studies in adults with acute coronary syndromes.…”
Section: Treatment Of Coronary Thrombosismentioning
confidence: 99%
“…According to Kato's report [4], the recurrent MI carries very high mortality rate. Therefore, the most effective way to prevent recurrent MI in Kawasaki disease is reduction thrombus size by early thrombolytic therapy [3]. The coronary artery bypass is another treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…12) Percutaneous transluminal coronary recanalization and intravenous coronary thrombolysis have been used to treat AMI in patients with KD. 13) A previous study has found that balloon angioplasty is not an effective means of revascularization in patients with coronary arterial stenosis due to KD because the lesions are stiff and often associated with calcification. 14,15) Moreover, as in our case 2, coronary aneurysms newly develop at sites of balloon dilatation in some patients.…”
Section: Discussionmentioning
confidence: 99%